Standard method of detailing structural concrete = a manual for best practice (Institution of Structural Engineers, 2006)
This document is intended to become a standard reference for work in structural design offices to be used in conjunction with the normal design codes and manuals. The objective has been to provide guidance of good practice and a working document on structural concrete that can be used to interpret the designers instructions in the form of drawings and schedules for communication to the site. This edition considers the effects, as far as possible, of Eurocode 2 on detailing principles and materials and attempts to provide guidance consistent with the Eurocodes. In addition, recent changes in practices and procurement of detailing services have been considered, such as the development of increased off-site fabrication and detailing being undertaken later in the construction sequence through initiatives such as contractor detailing. -- Provided by publisher.
Keywords: Reinforced concrete construction -- Details.; Structural drawing -- Standards.; elektronické knihy; electronic books